2022
DOI: 10.1111/1759-7714.14391
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of textbook outcome after lobectomy for early‐stage non‐small cell lung cancer in a Korean institution: A retrospective study

Abstract: Background Textbook outcome (TO) has been introduced as a novel composite measure for lung cancer surgery. We investigated TO after lobectomy for early‐stage non‐small cell lung cancer (NSCLC) in a Korean tertiary hospital and its prognostic implications for overall survival and recurrence. Methods Between January 2012 and December 2017, 418 consecutive patients who underwent lobectomy for clinical stages I and II NSCLC were identified and retrospectively reviewed. TO was defined as complete resection (negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…TOO parameters differ based on the databases used in each study, which may not be captured by NCDB. 1 , 2 , 3 In our study, we defined lymph node evaluation as ≥5 rather than 10. 32 In addition, NCDB does not have granular data to explain the reason for delayed chemotherapy initiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TOO parameters differ based on the databases used in each study, which may not be captured by NCDB. 1 , 2 , 3 In our study, we defined lymph node evaluation as ≥5 rather than 10. 32 In addition, NCDB does not have granular data to explain the reason for delayed chemotherapy initiation.…”
Section: Discussionmentioning
confidence: 99%
“…TOO is used for colorectal, upper gastrointestinal, and aneurysm surgery and has recently been explored in non–small cell lung cancer (NSCLC). 1 , 2 , 3 In NSCLC, TOO mandates surgical R0 resection, adequate lymph node resection for pathologic examination, timely receipt adjuvant therapy when indicated, and no prolonged length of hospital stay, 30-day mortality, reintervention, unplanned readmission, or major complications. Previous studies of stage I NSCLC demonstrated that TOO metrics were associated with superior overall survival (OS).…”
mentioning
confidence: 99%